Intensification of degradation of methomyl (carbamate group pesticide) by using the combination of ultrasonic cavitation and process intensifying additives - Raut-Jadhav, Sunita; Pinjari, Dipak V.; Saini, Daulat R.; Sonawane, Shirish H.; Pandit, Aniruddha B. (Ultrasonics Sonochemistry, 2016)
In the present work, the degradation of methomyl has been carried out by using the ultrasound cavitation (US) and its combination with H2O2, Fenton and photo-Fenton process. The study of effect of operating pH and ultrasound power density has indicated that maximum extent of degradation of 28.57% could be obtained at the optimal pH of 2.5 and power density of 0.155 W/mL. Application of US in combination with H2O2, Fenton and photo-Fenton process has further accelerated the rate of degradation of methomyl with complete degradation of methomyl in 27 min, 18 min and 9 min respectively. Mineralization study has proved that a combination of US and photo -Fenton process is the most effective process with maximum extent of mineralization of 78.8%. Comparison of energy efficiency and cost effectiveness of various processes has indicated that the electrical cost of 79892.34 Rs./m(3) for ultrasonic degradation of methomyl has drastically reduced to 2277.00 Rs./m(3), 1518.00 Rs./m(3) and 807.58 Rs./m(3) by using US in combination with H2O2, Fenton and photo-Fenton process respectively. The cost analysis has also indicated that the combination of US and photo-Fenton process is the most energy efficient and cost effective process. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Fenton; Hydrogen peroxide; Methomyl; Photo-Fenton; Synergistic coefficient; Ultrasound cavitation